Strategi Komunikasi Pemasaran Bank Syariah Indonesia KCP Bandung Citarum dalam Meningkatkan Loyalitas Nasabah - Maulana, Rifki; Adha, Mufti Alam (Musyarakah: Journal of Sharia Economic (MJSE), 2025)
This study examines the implementation of an Integrated Marketing Communication (IMC) strategy by Bank Syariah Indonesia (BSI) KCP Citarum to enhance customer loyalty. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings reveal that the IMC strategy incorporates advertising, direct marketing, online marketing, sales promotion, publicity, and public relations. However, challenges include low Sharia financial literacy, phishing threats, and a lack of professional marketing staff. Solutions proposed involve outreach to educational institutions, distributing cautionary brochures, and optimizing online marketing. The study concludes that an effective IMC strategy can improve customer loyalty in Islamic banking, provided that its unique challenges are addressed systematically.